A preliminary study of neuregulin 1 gene expression in schizophrenia patients on paliperidone in a Malaysian population in University Malaya Medical Centre (UMMC) / Nazariah Aiza Harun - Nazariah Aiza, Harun (2012)

(untitled)
BACKGROUND: The Neuregulin 1gene (NRG 1) polymorphism has been considered as a susceptibility gene for Schizophrenia. This is evident from studies done in several European and Chinese populations that suggesting a strong association between NRG 1 gene and Schizophrenia. There are numerous related studies worldwide and in Asian region but not in Malaysia that consists of 3 major races. Therefore, it is important for us to understand the reason for measuring NRG 1 gene expression given the importance of the gene as a risk factor for Schizophrenia, suggesting that NRG1 may have the potential as a biomarker for schizophrenia. OBJECTIVE: Schizophrenic patients on paliperidone treatment to be measured for NRG 1 gene expression. The aim of this study is to investigate NRG 1 gene expression in Schizophrenia subjects and the association of NRG 1 expression level with symptomatology. METHODOLOGY: This was a cross sectional study conducted in University Malaya Medical Centre (UMMC). Subjects were recruited from those attending the psychiatry and medical services in UMMC from February 2011 until November 2011 (10 months). The NRG 1 gene expression was measured for subjects on paliperidone treatment and in the control group. The information on socio-demographic (age, marital status, employment status) and clinical factors (family history of mental illness, duration of xx illness and psychopathology using Mini International Neuropsychiatric Interview (M.I.N.I) Positive And Negative Syndrome Scale (PANSS) and side effects using Barnes Akathisia Rating Scale (BARS) were collected. RESULT: A total of 20 Schizophrenia subjects and 15 healthy controls were recruited for this study. Among the 20 schizophrenia subjects majority were single (80%), unemployed (70%) and have family history of schizophrenia (55%). The average NRG 1 gene expression level in our 20 schizophrenia patients was 0.405 (SD= 0.491) and in the control group was 0.435 (SD= 0.273). No factors were found to be significantly associated with NRG 1 gene expression level. There was no significant association between NRG 1 gene expression level and psychopathology. CONCLUSION: The average NRG 1 gene expression level among Malaysians was 0.405 (SD= 0.491).Those with low PANSS score had lower NRG 1 levels (mean =0.304) compared to those with high PANSS score (mean = 0.524) and control group. This suggests that there is altered NRG 1 expression in Schizophrenic patients on Paliperidone in Malaysian population. In the future, a prospective study with larger sample size is needed to look further into this topic.